Thinness as Major Underlying Problem Among Adolescents of Northeast India - Mondal, N (Journal of Nepal Paediatric Society, 2014)
Background: Undernutrition is a major public health concern in many of the developing countries of Asia. Due to immense population size, socioeconomic disparities, illiteracy and inadequate access to health facilities prevalence is very high in India. The objective of this study was to determine the prevalence of age-sex specific thinness (low BMI-for-age) among adolescents residing in rural regions in India. Materials and Methods: This cross-sectional study has conducted among 1165 adolescent (602 boys; 563 girls) aged 10-18 years of Darjeeling district, West Bengal, India. Anthropometric measurements were height and weight obtained and BMI (weight/height2, kg/ m2) was calculated. The prevalence of thinness was assessed using newly proposed age-sex specific cut-offs of Cole et al. The data were analyzed using chi-square, ANOVA and Least Mean and Square (L,M and S) model approach. Results: Prevalence of overall thinness is 49.10% (51.16% boys, 46.89% girls) among rural adolescents. The boys are found to be more sufferer than girls in the different thinness grades include mild (grade I; 27.41% vs. 27.11%), moderate (grade II; 14.62% vs. 12.08%) and severe (grade III; 9.14% vs. 8.70%) (p>0.05). The age and sex specific smooth percentile curves of BMI were derived using L,M and S model approach for further evaluation of nutritional status. Conclusion: The existence of high prevalence of thinness among adolescents indicates nutritional deprivation among rural Indian adolescents. There is an urgent need of appropriate nutritional intervention program to address the public health problem related to undernutrition especially among nutritionally vulnerable segments of adolescents residing in rural regions to ameliorate the nutritional status DOI: http://dx.doi.org/10.3126/jnps.v34i1.8922 J Nepal Paediatr Soc 2014;34(1):39-47